A high-frequency dataset of sea level observations from low-cost pressure sensors - Lucia Pineau-Guillou; Pascal Lazure (Scientific Data)
Abstract A total of 30 low-cost bottom pressure sensors sampling at 2 Hz were developed and deployed in a nearshore environment during 4.2 months. The experiment took place in Blancs Sablons, a sandy bay near Le Conquet (France), during 2023–2024 winter. All the 30 sensors were successfully recovered. Among them, 22 sensors functioned properly recording full data, 5 sensors partially recorded data due to battery failure or malfunctioning, and only 3 sensors did not work, due to small holes in their plastic protection. Comparison with a commercial pressure gauge revealed the good performance of the low-cost sensor, with a large autonomy, few missing data, and a robust wave-to-wave comparison. However, a small drift of around −0.001 bar/month was detected. Pressure data were converted into sea levels, related to Chart Datum, and validated against permanent instruments (wave buoy and tide gauge) located close to the site. The high-frequency dataset can now be used to validate ocean and wave models, or fine scale altimetry missions such as SWOT (Surface Water and Ocean Topography).